An analysis of K-12 education reform in Kansas: a case study of state-level policy actors and neoliberal policies - Allen, Katie Lynn (Kansas State University, 2019)
At the national and global levels, education policy is widely considered to be increasingly framed by market-oriented ideas often pushed by elite special interest groups. These groups use their collective power to influence legislators’ decisions, often stifling improvement efforts and contradicting research evidence. Public choice theory contends that elected-officials seek personal benefit in policy decisions, framing the role of special interest groups as a malevolent force. The purpose of this study is to better understand state legislative policy making, with a specific focus on the role of special interest groups, their policy preferences, and the strategies they employ. This research answers the question: How do special interest groups influence K-12 education policy at the state-level? The State of Kansas’ 2013-2018 House and Senate Education Committee sessions provide material for this qualitative multi-case study. Three hundred eighty-three pieces of testimony were analyzed for content. Sixteen semi-structured interviews with lobbyists, state-elected officials, bureaucrats, and public, private, and religious school leaders were conducted to explore differing perspectives and further understand policy discourse strategies. Data were analyzed using NVivo qualitative data analysis software. Themes in testimony were aggregated as well as compared by special interest group and policy position on six key issues. Shifts toward a neoliberal framing of education at the state-level is evident, including efforts to deregulate the teaching profession, policies that allow the state to fund private education, and public appeals for less government. Findings indicate policy discourse is dominated by education-affiliated special interest groups who often work in tandem toward securing resources, with primary opposition preferences promoting free-market ideology and low taxes. Discourse illustrates that public opinion is shaped by mainstream conservative ideology slowly moving education toward market-based principles. Educators resist change through the discourse of local control while strengthening public accountability of elected officials through insistence on checks and balances in government. Results indicate that many special interest groups undertake a democratic process open to their members to determine their collective policy position and remind lawmakers of their collective voting power. Professionals utilize scientific dialect on occasion to make rational arguments, but ideological discourse about the perceived role of government and personal stories and experiences dominate testimony. A lack of reliance on research evidence is perhaps due to the complexity of policy issues or possibly reflects the power of storytelling as a strategy to influence elected officials. However, interviewees shared that distrust amongst special interest groups and perceived bias of information sources conceptualizes facts and evidence-based data as subjective. Ultimately, the legislator ends up relying on inductive processes to affirm beliefs that tend to align with the majority of the electorate. This supports the premise that public choice theory, rather than research-based evidence guides state-level policy decisions. Implications for policymakers include developing policy that supports student achievement above all else and increase the utilization of evidence-based research in decision-making. Results indicate a need for more effective methods to shape public opinion in support of education. Suggestions for education advocates to successfully engage in political discourse are provided.
Keywords: Political discourse; K-12 education; Qualitative case study; Special interest groups; Public choice theory